UTILIZATION OF SOCIAL MEDIA FOR WEBSITE-BASED SALES APPLICATIONS AT PT TIRTHO ALAM LESTARI - Tito Akbar Firmanda; Tan Amelia; Henry Bambang Setyawan (Jurnal Sistem Informasi Universitas Dinamika, 2022)
The company PT Tirtho Alam Lestari is engaged in the procurement of products around safety and rescue equipment. This company serves various types of customer requests for safety and rescue equipment throughout Indonesia, especially on the island of Java. In this company, there are several obstacles, namely the company carries out the sales process by visiting customers directly and in recording sales reports written manually on books which causes the reports to be damaged or lost. Therefore, in this research, a solution is given in the form of using social media for a sales website application based on PT Tirtho Alam Lestari. The application was developed using the Waterfall method which consists of 4 stages, namely Communication, Planning, Modeling, and Construction. The application generated from this research includes features for customers in the form of sign up, login, display of all products sold, and customers can order products sold. Furthermore, there are features for admins in the form of dashboards, product views (can be added, deleted and edited), product categories, all orders, also generate best-selling product reports, revenue graph reports, and all orders reports. The application is also equipped with the use of social media, namely WhatsApp to support the system, including being able to send automatic replies from the admin, broadcast marketing and confirmation of payments from customers. Based on the results of trials with User Acceptance Testing with an average ratio obtained of 81%, which can be said that this application can be accepted by users.Keywords: Utilization of Social Media, Web Application, PT Tirtho Alam Lestari